DIAKOME EN DIGITALISERING: SENDINGREKORDS EN GESKIEDEMS IN DIE 21 STE EEU (Historia, 2021)
EnglishResearch on the history of Christian missions and mission stations have for long been neglected in South African historiography. With the advent of the new constitutional dispensation in 1990, and the empowerment of the majority of the population - often those stemming from communities where mission stations played a major role in the development of these groups - individuals and groups now rediscover the importance of local history. Parochial church records play an important role in reconstructing the lives and history of these communities.Very few mission societies established their own archives and researchers usually have to consult the documents at the various mission stations and churches where the documents are physically kept - often under adverse conditions.In this article the researcher explains how the latest photographic technology might help historians. The digital capturing of images allows the historian to copy these records in a time- and cost-effective way, without damaging the often fragile documents.  AfrikaansNavorsing op die terrein van die Christelike sending en sendingstasies was vir 'n lang tyd verwaarloos in die Suid-Afrikaanse gerskiedskrywing. Kerklike rekords en dokumente is selde deur historici in Suid-Afrika benut. Met die konstitusionele verandering wat in 1990 tot stand gekom het, en die bemagtinging van die meerderheid van die bevolking - wat dikwels rondom sendingstasies ontwikkel en gegroei het - is daar by talle individue en groepe 'n nuwe belangstelling in plaaslike geskiedenis. Gemeentelike rekords is onontbeerlik vir die rekonstruksie van die verlede van hierdie gemeenskappe.Slegs enkele sendinggenootskappe se dokumente word in argiefbewaarplekke bewaar en navorsers moet gewoonlik die - dikwels gehawende - dokumente op afgeleë sendingstasies raadpleeg.In hierdie artikel verduidelik die navorser hoe die jongste fotografiese tegnologie vir historici van waarde mag wees. Die digitale vaslegging van dokumente stel die historikus in staat om hierdie materiaal op 'n tyden koste-effektiewe wyse te kopieer sonder om die dikwels brose dokumente te beskadig.
Keywords: Nederland; Dr. Hans Heese; Historiese Navorsing van UWK; Anna Böeseken; Con de Wet; Theal; mikroverfilming; Parys; George Mc Carthy; Historia 1998